Twelfth night, or, what you will - Shakespeare, William 1564-1616 (The Arden Shakespeare. Third series, 2008)
"This edition of Twelfth Night provides: a clear and authoritative text, edited to the highest standards of scholarship; detailed notes and commentary on the same page as the text; a full, illustrated introduction to the play's historical, cultural and performance contexts; an in-depth survey of critical approaches to the play; a full index to the introduction and notes; and a select bibliography of references and further reading."--Jacket.